Distribution of the spectrum and representation of solutions of degenerate dynamical systems - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We propose algebraic methods for the investigation of the spectrum and structure of solutions of degenerate dynamical systems. These methods are based on the construction and solution of new classes of matrix equations. We prove theorems on the inertia of solutions of the matrix equations, which generalize the well-known properties of the Lyapunov equation.